The effect of health media in reminiscence therapy on cognitive disorders in post-stroke patients - Manurung, Sarida Surya; Sudiana, I Ketut; Haryanto, Joni; Siregar, Sarmaida; Manurung, Jonni Sastra; Ritonga, Abdul Malik (Gaceta Médica de Caracas, 2024)
Introduction: One of the psychosocial obstacles that often arise in post-stroke patients is cognitive obstacles. These obstacles include various problems in cognitive function, ranging from disturbed attention and difficulty in maintaining orientation to time, place, or situation to problems in memory and thought processes. This study aims to investigate the effect of health media in reminiscence therapy on cognitive disorders in post-stroke patients in Medan City. Methods: This research uses quantitative research methods. Data was collected by distributing questionnaires to respondents in seven hospitals in Medan City.